EFFICACY OF INTRAVITREAL TRIAMCINOLONE ACETONIDE FOR DIABETIC MACULAR EDEMA - Gautam, Prachand; Shrestha, Koshal; Lamichhane, Gyanendra; Patel, Sushila (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Diabetic retionopathy is a microangilpathy. The present study was done to investigate results of Intravitreal Triamcinolone Acetonide injection for the treatment diffuse diabetic macular edema. MATERIAL AND METHODS: The study included 40 eyes of 40 patients with clinically significant diffuse diabetic macular edema. Eyes were diagnosed with diabetic macular edema according to Early Treatment Diabetic Retinopathy Study guidelines. An Intravitreal injection of Triamcinolone Acetonide at the dose of 4 mg/0.2 ml was administered. Best corrected visual acuity was measured as the logarithm of the minimum angle of resolution (logMAR) and snellen vision drum and size of macular edema (hard exudates) was obtained by slit lamp biomicroscopy using +90 D Volk lens at each visit. Intraocular pressure (IOP) and other complications related with steroid and injection related complications were also evaluated. Subsequently patients were followed up on 1st day, 2nd week and 3rd month. RESULTS: All patients were completed second follow up at 3 months. The mean size of macular edema, which obtained at 3 months postoperatively, was significantly different from the baseline measurement from 1.4125 to 0.9474 DD. Mean visual acuity improved significantly from baseline at 3 months of follow up was 0.7421 LogMAR (≈ 6/30 in Snellen chart). Eleven eyes developed intraocular pressure higher than 21 mmHg at 2nd week postoperatively. Other drug and injection related complications were not developed. Increased IOP were controlled with anti glaucoma drugs. CONCLUSIONS: Intravitreal Triamcinolone was a promising therapeutic method for diabetic macular edema. TriamcinoloneAcetonide effectively reduces size of macular edema and improves visual acuity in the short term. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 30-34